Inclusive Education Practices: A Systematic Literature Review on Approaches and Impact - Arman Paramansyah (Penelitian dan Pengembangan Ilmu, 2024)
This research discusses approaches to inclusive education, including Universal Design for Learning (UDL), Differentiated Instruction, Collaborative Teaching, and the Use of Supporting Technology, as well as the formation of positive Attitudes and Perceptions. By utilizing various literature sources, this research identifies the impact and implications of each approach on academic, social, emotional and attitudinal dimensions in the context of inclusive education. The findings show that these approaches have great potential to improve educational outcomes and create a more inclusive and empathetic society. However, the study also underscores the need for further research to explore the limitations, implementation, and long-term impacts of these approaches, as well as efforts to integrate advanced technologies in inclusive educational practices.